Role of Biomass in Urban Energy Management - Szendrei, János; Kocsi, Balázs; Szűcs, Edit (International Journal of Engineering and Management Sciences, 2018)
When making decisions on the use of energy, both on building and on city level, biomass plays certainly a role in looking for sustainable solutions. This study starts with highlighting some key points regarding urban energy management, including world urbanization trends, heat island effect of big cities and energy hierarchy in energy management. With these in mind, it is worth considering, how the shading effect of surrounding biomass can mitigate the heating needs as a wind barrier in the winter or decrease the cooling load as shadowing element in the summer, both for buildings and whole cities. These can be further enhanced by biomass integrated in the buildings’ envelope: green roofs and green walls can have significant energy conservation effects, according the characteristics of their different types. Lastly, urban disposal of biomass can lead to renewable energy generation, both in case of biogas production and waste incineration. These shading, covering and fuel possibilities all underline the importance of biomass in urban energy management.